2010
DOI: 10.1088/0965-0393/18/8/085008
|View full text |Cite
|
Sign up to set email alerts
|

Screw dislocation mobility in BCC metals: the role of the compact core on double-kink nucleation

Abstract: In this work, we examine the kink-nucleation process in BCC screw dislocations using atomistic simulation and transition pathway analysis, with a particular focus on the compact core structure. We observe the existence of a threshold stress, which results in an abrupt change in the minimum energy path of the kink-nucleation process, and hence, a discontinuity in the activation energy versus stress for the process. The magnitude of the discontinuity is found to be related to the degree of metastability of an in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
55
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(74 citation statements)
references
References 37 publications
3
55
0
1
Order By: Relevance
“…While this result may not appear at first to be very surprising as a sinusoidal potential is an obvious choice, Hirth and Lothe 32 have pointed out that this is a model potential and may not accurately describe the potential shape in real materials. Furthermore, the empirical potentials, as noted here and shown in other studies 15,16 , often predict a double maximum (camel hump) Peierls potential. Thus, the prediction of a common sinusoidal potential may be regarded as quite surprising.…”
Section: B Dft Predictionssupporting
confidence: 81%
See 3 more Smart Citations
“…While this result may not appear at first to be very surprising as a sinusoidal potential is an obvious choice, Hirth and Lothe 32 have pointed out that this is a model potential and may not accurately describe the potential shape in real materials. Furthermore, the empirical potentials, as noted here and shown in other studies 15,16 , often predict a double maximum (camel hump) Peierls potential. Thus, the prediction of a common sinusoidal potential may be regarded as quite surprising.…”
Section: B Dft Predictionssupporting
confidence: 81%
“…This is in agreement with recent DFT calculations of the core structure in iron 23 that showed a Peierls potential that is sinusoidal in shape and lacks a metastable split core structure. These results suggest that empirical potentials are often incorrect, as they frequently predict either a degenerate core structure or a compact core structure along with the split core structure 15 . It therefore seems prudent to use the Peierls potential as either part of interatomic potential development in BCC metals or as part of their validation if the potentials are meant to predict properties of BCC screw dislocations, an approach recently taken for the development of BCC iron potentials 54 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the literature various studies can be found to deal with the dislocation mobility using molecular dynamics simulations. However, they are all limited to simple systems and they do not attempt to calculate the effect of the concentration on the mobility [42][43][44]. Recently work has been done in calculating the mobility of screw dislocations in α-iron and to derive analytical expressions for the use within the dislocation dynamics [45].…”
Section: Introductionmentioning
confidence: 99%